2016
DOI: 10.12740/app/61977
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depressive and anxiety disorders in dialysis patients with chronic kidney disease

Abstract: SummaryAim: The objective of this study was to assess the prevalence of depression in dialysis patients and its relationship with attitude toward illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 17 publications
3
25
2
Order By: Relevance
“…However, a cross-sectional survey conducted in Pakistan in 2013 that used the same HADS questionnaire estimated a higher prevalence of anxiety and depression among patients on hemodialysis: 57.30% of their sample had depression and 42.69% had anxiety disorders [14]. Another study found that depressive disorders were diagnosed in 78.5% of patients on dialysis [15]. However, these discrepancies in the frequency of depression may be attributed to differences in population and the smaller sample size of patients in this study, in addition to socioeconomic differences between the populations.…”
Section: Discussionmentioning
confidence: 99%
“…However, a cross-sectional survey conducted in Pakistan in 2013 that used the same HADS questionnaire estimated a higher prevalence of anxiety and depression among patients on hemodialysis: 57.30% of their sample had depression and 42.69% had anxiety disorders [14]. Another study found that depressive disorders were diagnosed in 78.5% of patients on dialysis [15]. However, these discrepancies in the frequency of depression may be attributed to differences in population and the smaller sample size of patients in this study, in addition to socioeconomic differences between the populations.…”
Section: Discussionmentioning
confidence: 99%
“…6 The rate of depression is three times higher in ESRD patients than in the general population. 7 Depression in HD patients is associated with various factors, including gender, marital status, 6 ethnicity, 7 QoL, 8,9 acceptance of the illness, 10 dialysis shift, 11 and anxiety. 8,9 Seasonal variability of depressive symptoms has also been found in HD patients.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Mental health issues such as anxiety and depression also increase patients risk of morbidity and mortality, yet these issues are underdiagnosed and undertreated. [4] One component of the treatment experience thought to impact negatively on mental health and wellbeing is the issue of empty time during haemodialysis, [3] where there is limited opportunity to engage in meaningful activities, creating profound boredom resulting in rumination and contemplation of illness and death. [5] Time can also be warped for patients during haemodialysis, as patients report time 'dragging' while watching the clock.…”
Section: Introductionmentioning
confidence: 99%